2020
DOI: 10.1007/s13205-020-02194-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of hydrogen cyanamide (HC) in grape bud dormancy release: proteomic approach

Abstract: In the present study, we identified changes in protein expression patterns of grapevine buds when treated with hydrogen cyanamide (HC). HC induced a shift of more than 2-folds in the expression of 1250 proteins out of approximately 7000 detected proteins. The majority of the differentially expressed proteins (DEPs) were localized in the chloroplast (419) and cytoplasm (347). Most of the detected DEPs were linked with energy metabolism, redox activity, hormone, and stress signaling. Particularly, the DEPs assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Growing blueberries in a greenhouse can enable plants to resist cold and promote their growth and early flowering and fruiting [30] and is widely practiced in northeast China. Hydrogen cyanamide has been effectively used to advance bud breaking [19] and promote early ripening in deciduous fruit trees [31]. It has also been reported that HC application can increase yield in 'Perlette' grape (Vitis vinifera L.) [32] and pistachio (Pistacia vera L.) [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing blueberries in a greenhouse can enable plants to resist cold and promote their growth and early flowering and fruiting [30] and is widely practiced in northeast China. Hydrogen cyanamide has been effectively used to advance bud breaking [19] and promote early ripening in deciduous fruit trees [31]. It has also been reported that HC application can increase yield in 'Perlette' grape (Vitis vinifera L.) [32] and pistachio (Pistacia vera L.) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Due to insufficient chilling requirements in the greenhouse, delayed and irregular bud breaking and flowering often occur, resulting in a decrease in blueberry yield or even no harvest. A large number of studies have demonstrated that dormancy breaking agents such as HC can substitute part of the chilling requirements, advance and synchronize bud breaking and blooming, and hasten fruit maturity [19][20][21][22]. The application of dormancy breaking agents will be an important strategy to promote the early ripening of fruits in blueberry greenhouse production.…”
Section: Introductionmentioning
confidence: 99%